Las huellas de "El Dorado" en el Valle del Alto Huallaga: Estado, coca(ína) y desborde popular en las fronteras del capitalismo andino amazónico - Gaitero, Francisco Javier Mazeres (Universidade Federal de São Carlos, 2020)
The Alto Huallaga Valley, rural territory of the Peruvian Andean Amazon, has been associated with long-lasting social representations that mainly relate it to drug trafficking and political violence. Despite its high historiographic detachment, this image has played an essential role in quenching the repertoires of resistance that the peasant movement has been displaying in response to the asymmetries that the republican national project has triggered in the region. After a secular abandonment and in a kind of continuity with colonial projects, the mercantile turn has been expressed here, between political messianism and exceptional languages, through a developmental discourse on population, market and territory. And it has done so throughout its four different constitutive cycles: i) colonization projects, ii) the cocalization of its economy, iii) the armed conflict and iv) the policies of the so-called "alternative development". This study, halfway between oral history and ethnographic work, eclectic from the methodological point of view, aims to reconstruct, in its complexity, the social history of Alto Huallaga; critically contrasting the official account with the experiences of the peasant sectors that express the social impact and the limits of the modernizing project. Likewise, it seeks to enhance a ruralistic, diachronic and subordinate perspective that replaces the centrality that until today the security dimension of the conflict have deserved. Finally, it is hoped to contribute to rethinking the historical fabric of contemporary Peruvian society, without losing the perspective of the subjects located on its margins.

El Valle del Alto Huallaga, territorio rural de la selva andino amazónica peruana, ha estado asociado a representaciones sociales duraderas que lo relacionan principalmente con el narcotráfico y la violencia política. A pesar de su alto desapego historiográfico, esta imagen ha jugado un papel esencial a la hora de apagar los repertorios de resistencia que el movimiento campesino ha ido desplegando en respuesta a las asimetrías que el proyecto nacional republicano ha desencadenado en la región. Luego de un secular abandono y en una suerte de continuidad con los proyectos coloniales, el giro mercantilista se ha expresado aquí, entre el mesianismo político y los lenguajes de excepción, a través de un discurso desarrollista sobre población, mercado y territorio. Y lo ha hecho a lo largo de sus cuatro distintos ciclos constitutivos: i) los proyectos de colonización, ii) la cocalización de su economía, iii) el conflicto armado y iv) las políticas del llamado “desarrollo alternativo”. Este estudio, a medio camino entre la historia oral y el trabajo etnográfico, ecléctico desde el punto de vista metodológico, plantea reconstruir, en su complejidad, la historia social del Alto Huallaga; contrastando críticamente el relato oficial con las experiencias de los sectores campesinos que expresan el impacto social y los límites del proyecto modernizador. Asimismo, se busca realzar una perspectiva ruralista, diacrónica y subalterna que reemplace la centralidad que hasta hoy han merecido la dimensión seguritaria del conflicto. Finalmente, se espera contribuir a repensar la trama histórica de la sociedad peruana contemporánea, sin perder la perspectiva de los sujetos situados en sus márgenes.
As pegadas de "El Dorado" no Valle del Alto Huallaga: Estado, coca(ina) e agitação popular nas fronteiras do capitalismo andino amazônico
The footprints of "El Dorado" in the Valle del Alto Huallaga: State, coca(ine) and popular overflow on the borders of andean amazon capitalism
Keywords: Peru; Mundo rural; Políticas de povoamento; Mercado local; Produção de drogas; Conflito armado; Desenvolvimento alternativo; Rural world; Settlement policies; Drug production market; Internal armed conflict; Alternative development; CIENCIAS HUMANAS::SOCIOLOGIA::SOCIOLOGIA RURAL